Seasonal Related Multifactorial Control of Pituitary Gonadotropin and Growth Hormone in Female Goldfish: Influences of Neuropeptides and Thyroid Hormone - Ma, Yifei; Ladisa, Claudia; Chang, John P.; Habibi, Hamid R. (Frontiers in Endocrinology, 2020)
Female reproduction is under multifactorial control of brain-pituitary-peripheral origin. The present study provides information on seasonal changes in circulating LH and GH concentrations, as well as transcript levels for a number of genes involved in the regulation of reproduction and growth in female goldfish. We also provide information on the effects of treatments with GnRH and/or GnIH, and their interaction with T3, at three stages of gonadal recrudescence. Maximum basal concentration of LH was observed at late recrudescence (Spring) while no seasonal changes in basal serum GH levels was detected. Serum LH and GH levels were stimulated by GnRH as expected, depending on the season. GnIH stimulated basal GH concentrations in gonadally regressed fish. GnIH inhibitory action on GnRH-induced LH response was observed in late, but not in mid recrudescence. T3 actions on basal and GnRH- or GnIH-induced GH secretion were generally inhibitory, depending on season. Administration of T3 attenuated GnRH-induced LH responses in mid and late stages of gonadal recrudescence, and the presence of GnIH abolished inhibitory actions of T3 in fish at mid recrudescence. Our results also demonstrated seasonal patterns in basal and GnRH- and/or GnIH-induced transcript levels for ERα, ERβI, FSHR, aromatase, TRαI, TRβ, IGF-I, and Vtg in the liver and ovary. However, there were no clear correlations between changes in transcript levels and circulating levels of LH and GH. The results support the hypothesis that GnRH, GnIH, and T3 are contributing factors in complex reciprocal control of reproduction and growth in goldfish.